2022
DOI: 10.4067/s0717-92002022000100069
|View full text |Cite
|
Sign up to set email alerts
|

Water regime and substrate influence the growth of Eugenia uniflora seedlings

Adriana Maria Griebeler,
Maristela Machado Araujo,
Felipe Turchetto
et al.

Abstract: Eugenia uniflora is a fruit tree of the Myrtaceae family, native to Brazil, Argentina and Uruguay that has high potential for use in landscape and environmental projects, food and pharmaceutical industry. However, information on the production of quality seedlings is still scarce. The objective was to identify the appropriate substrate and its characteristics, in relation to the water regime for the production of E. uniflora seedlings. The experiment was conducted in a randomized block design, in a factorial s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This polymer have the capacity to absorb water during periods of water availability and release it to the roots of plants when there is a deficit in the soil (Leciejewski, 2009). Previous studies have already shown positive effects of hydrogel on tree nursery-grown seedling development (Griebeler et al, 2022;Turchetto et al, 2020). However, studies that evaluate its effectiveness in direct sowing of forest species are scarce (Souza, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This polymer have the capacity to absorb water during periods of water availability and release it to the roots of plants when there is a deficit in the soil (Leciejewski, 2009). Previous studies have already shown positive effects of hydrogel on tree nursery-grown seedling development (Griebeler et al, 2022;Turchetto et al, 2020). However, studies that evaluate its effectiveness in direct sowing of forest species are scarce (Souza, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Inoculation of Trichoderma spp. and hydrogel application already have been tested in forestry and agriculture to promote increased germination and growth of seedlings in nursey, maximize water availability, and improve microclimatic and edaphic conditions in the field (Griebeler et al, 2022;Racic et al, 2018;Sankar et al, 2019), however, its potential beneficial effects on tree species performances in direct seeding techniques for forest restoration have not been studied yet. Thus, the study was carried out to evaluate the influence of the use of Trichoderma asperelloides and hydrogel alone, or in combination, in the direct sowing of five native forest tree species as a strategy for the enrichment of the area in the initial restoration process, in the extreme south of the Atlantic Forest Biome.…”
Section: Introductionmentioning
confidence: 99%